Thermomigration induced degradation in solder alloys - Basaran, C.; Li, S.; Abdul Hamid, M. F. (State University of New York at Buffalo, USA, 2008)
Miniaturization of electronics to the nanoscale brings new challenges. Because of their small size and immense information and power processing capacity, large temperature gradients exist across nanoelectronics and power electronics solder joints. In this paper, a fully coupled thermomechanical-diffusion model is introduced to study the thermomigration induced strength degradation. A nonlinear viscoplastic material model with kinematic and isotropic hardening features is utilized. The model takes into account microstructural evolution of the material. A grain coarsening capability is built into the model to study its influence on thermomigration in solder alloys. The model is validated by comparing the simulation results with experimental data.